A RESEARCH ON SELF DESIGN OF RELIGIOUS STAFF CANDIDATES - Abdulkadir ÇEKİN (Fırat University, 2019)
The mission of The Presidency of Religious Affairs in common religious education may be summarized as raising the awareness of the public about the religion and managing the religious ministries. Religious staff -responsible to lead discharging of the religious duties and to raise the awareness of the public about the faith, worship and morality subjects- are the primary element of common religious education. Having very old origin, the institution of religious staff sometimes got active roles, sometimes limited services to a mosque in historical periods. However, the institution has been known to be one of the most important factors, especially in adult religious education activities, for adult in